Determination of the Shelf Life of Wet Sago Noodles Produced by Pondok Sagu Metro - Indah Yuliasih; Mirsa Armana (UNIVED Press, Dehasen University Bengkulu, 2026)
Purpose : This study aims to determine the shelf life of wet sago noodles produced by Pondok Sagu Metro whose shelf life is unknown. Methodology: This study was conducted using the Extended Storage Studies (ESS) method, with the treatment of wet sago noodle products in embossed vacuum plastic stored at two storage conditions, namely: at a temperature of 2-8°C with RH 85% (chiller temperature) and a temperature of 25°C with RH 41% (room temperature). Observations were made every day for 7 days on the parameters of mouisture content, Total Plate Count (TPC), and organoleptic tests. Results: The shelf life of wet sago noodles based on the Total Plate Count (TPC) value is 5 days at room temperature and 7 days at chiller temperature. Findings: For products that are easily damaged by microorganisms, the shelf life of the product can be written as the use by date on the packaging label. Novelty: Determining the shelf life of products based on the relationship between TPC value parameters and organoleptic tests has not been widely carried out. Originality: This study used wet sago noodles produced by Pondok Sagu Metro as a test sample, so it can be used as a reference for listing the expired date. Conclusion: Differences in storage conditions affect changes in the TPC value and organoleptic test of wet sago noodles during storage, but do not affect their mouisture content. Type of Paper : Research Article.